From Gendered Subalternity and Marginality to Gendered Revolution and Empowerment: Mao Dun's “Creation” as an Epitome of Nora-ism. - Lakshmi. R. Nair (Singularities : A Transdisciplinary Biannual Research Journal, 2016)
“It is no exaggeration to say that the women's movement in the May Fourth period is nothing but Noraism ... Nora's spirit to “be a human being,” her realisation that besides being a mother and wife she is a person, and her idea of “the responsibilities she as a person has” are all healthy, progressive thoughts, even for us today.” - Mao Dun, 1938. Mao Dun's revolutionary short story “Creation” reflects the iconoclastic spirit of Chinese May Fourth Period, expresses the female personality liberation movement, and criticizes the male chauvinistic mentality - to change the female destiny under the thumb of culturally institutionalized patriarchy. It explores the New Woman and exposes the transformations that redefine the gendered identities under the discourse of cultural modernity dominated by maleficent system. It dramatises the construction of female intellectual's self-identity and feminine Nora-esque dominance over malevolent hegemony. It invokes the traditional discourses of female virtue versus the revolutionary discourses of female enlightenment with the influence of dominated male-driven discourses on revolution and modernisation. It reveals the contradictions inherent in male-guided modernisation project that socially prescribed the female gender identities and the complex relationships between traditional culture norms and contemporary iconoclastic ideals. The aim of the researcher is to identify the masculine dominance over female identity, and examine the resurrection of female gender from patriarchy. “Creation” contextualizes the reinforcement of gender stratification, gender bifurcation consciousness, gender terminology, intersectionality, and conflict theory in culture by highlighting gender bending, gender dynamics, and gender configuration. It represents the female political potency and male castration anxiety; and contradicts the hegemonic masculinity and emphasized femininity. It deploys extreme male power since Junshi (the male dominated husband) wants 'to create' a doll-like subordinate Xianxian (the gendered subaltern wife) for his personal gratification. For him, she is not a human being with her own unique identity, but a performer for his desires and fulfilments. Initially, he convinces her about his “ideal” dream-like woman with his influence, but finally, she shatters his “ideal” with her own interpretations and findings. Here, the husband envisages an image of the superior-Self in the inferior-Other and establishes a discursive control over his female counterpart for maintaining his coherent identity as a modern male. But, the wife subverts the authority of masculine position and challenges the male gender power. Junshi acts as a colonizer with his Calibanistic motto in creating an “ideal” Xianxian for his personal whims, and thereby her individual self identity is colonized and destroyed. “Creation” is a paradoxical discourse of masculine anxiety about feminism. “Creation” is examined with the nexus of theory and politics of Judith Butler's 'gender trouble and performativity,' Elaine Showalter's 'female malady and gender wilderness,' Dorothy Smith's 'gender bifurcation consciousness,' and Patricia Collins's 'domination matrix and epistemology.'